Rancang Bangun Solar Tracker dengan Sensor Light Dependent Resistor Berbasis Arduino - Aditya W Utama (JURNAL CITRA WIDYA EDUKASI, 2019)
The problem always occurs with solar panel users, is the efficiency of solar panels and monitoring of solar panel generating systems. This causes the need for a solar tracker and monitoring system. The tracker system functions to increase the productivity of solar panels and the monitoring system serves to provide information on the condition of the productivity of solar panels. Internet of Things (IoT) allows devices to communicate like sending and receiving data. This study designed a tracker and monitoring system consisting of Arduino Mega, Esp8266-12F, LDR sensors and servo motors. Simple web application is able to provide information in realtime to users, so they can monitor the productivity of solar panels. When the solar panel generates electricity and passes the INA219 current sensor, the sensor will send an analog signal to Arduino Mega which will be forwarded to Esp8266 to send sensor data information sent to a simple web, then the data is accessed by the Google Chrome application as a user interface. The LDR sensor can detect the level of sunlight and send a signal to arduino mega which will then be processed and send commands to the servo motor to move following the arduino mega command to the direction of the light source.